Meningkatkan Kemampuan Berkolaborasi Melalui Pendekatan Tutor Sebaya dalam Pembelajaran Berdiferensiasi - Siti Luthfah Ridwan (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
Large classes with diverse learning needs become obstacles for teachers in providing intensive individual assistance for learning outcomes in identifying interactions between living things and their environment. Differentiated learning can be a solution. This research aims to see whether there is an increase in students' collaboration abilities through the peer tutoring approach in differentiated learning. This research is classroom action research carried out in two cycles starting from planning, implementation, observation and reflection. The research instruments used observation sheets and cognitive level learning outcomes tests. The results showed that student collaboration increased by 37.50% and cognitive level learning outcomes increased by 39.50% from cycle I to cycle II. The implementation of learning which has implications for obtaining these results increased by 12.0%. It can be concluded that there has been an increase in the ability to collaborate through the peer tutoring approach in differentiated learning in the learning outcomes of identifying living things and their environment in class VII of SMP Negeri 3 Gorontalo. It can be concluded that there has been an increase in the ability to collaborate through the peer tutoring approach in differentiated learning in the learning outcomes of identifying living things and their environment in class VII SMP Negeri 3 Gorontalo.